Effect of the Cycle Size and Spacer Structure in Tacrine and its Cyclopentyl Homologue Conjugates with 5-(4-trifluoromethyl-phenylamino)-1,2,4-thiadiazole on the Spectrum of their Biological Activity - Kovaleva, N.V.; Proshin, A.N.; Rudakova, E.V.; Boltneva, N.P.; Serkov, I.V.; Makhaeva, G.F. (Biomedical Chemistry: Research and Methods, 2018)
The conjugates of tacrine and its cyclopentyl analogue with 5-(4-trifluoromethyl-phenylamino)-1,2,4-thiadiazole, combined with two different spacers, pentylaminopropane and pentylaminopropene, were synthesized. Their esterase profile, the ability to displace propidium from the peripheral anionic site (PAS) of acetylcholinesterase (AChE) and antioxidant activity in the ABTS test were investigated. The compounds obtained effectively inhibit cholinesterases with a predominant effect on butyrylcholinesterase, displace propidium from the PAS of Electrophorus electricus AChE (EeAChE) and exhibit a high radical-scavenging capacity. It is shown that, depending on the spacer structure, particulary, the presence of a propenamine or propanamine fragment, the spectrum of biological activity of the conjugates changes.